Mathematics-Based Development Module Guided Discovery Model to Improve Creative Thinking Ability - Utami, Tatik Susilowati; Suparman, S (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2018)
Creativity is one of the abilities students must possess in learning mathematics. This study aims to produce mathematical modules based on discovery models guided by arithmetic rows and series for students of class X SMK. This research is a 4D model development research consisting of four stages: define, design, develop, disseminate. Research subjects included media experts, material experts, students from 2 schools in 2 Muhammadiyah Vocational Schools in Yogyakarta and Cangkringan Muhammadiyah Vocational Schools. Data collection techniques in the form of questionnaires and tests. The research instrument is a questionnaire that has been reviewed. Data analysis techniques used qualitative analysis which was changed to a cumulative Likert scale. The results of the material feasibility test were in a very good category with an average score of 107. The results of the module media feasibility test were in the very good category with an average score of 98.33. While the results of the student response questionnaire on the trial of small class products included in the good category with an average score of 92.33. And the results of student responses to the trial of large class products are included in the good category with an average score of 91.45. So the mathematics module based on guided discovery models on sequence and sequence series material.